Working fluid parametric analysis for regenerative supercritical organic Rankine cycles for medium geothermal reservoir temperatures. (September 2017) - Moloney, Francesca; Almatrafi, Eydhah; Goswami, D.Y.
Abstract: The conversion efficiency of geothermal energy is very low. For low-temperature resources, such as geothermal energy, a supercritical organic Rankine cycle (ORC) has been shown to be more efficient than an ORC. Regenerative supercritical ORCs have been proven to yield even higher efficiencies for cases where the heat source is limited above the ambient temperature. Most studies on these cycles have focused on turbine inlet temperatures between 80 and 130˚C. Only a few studies have explored other working fluids between 180 and 350˚C but did not analyze optimum turbine inlet pressures. Turbine inlet temperatures ranging from 170 to 240˚C were tested with the heat source provided by a medium temperature geothermal reservoir. A parametric analysis was performed for various turbine inlet pressures and temperatures. The fluids tested included cis-butene, pentane, isopentane, butane, isobutane, carbon dioxide, neopentane, propylene, and propane. Temperatures and pressures were selected for each tested fluid to achieve maximum first law efficiency, second law efficiency, cycle effectiveness, and net work.